STUDIES ON MORPHOLOGY, GROWTH HABIT, HYPHAL ANASTOMOSIS AND VIRULENCE PATTERN OF FIVE ISOLATES OF SHEATH BLIGHT PATHOGEN OF RICE - AND A. P. K. REDDY, S. K. SINGH*, K. SATYANARAYANA (Indian Phytopathology, 2002)
Isolations from the diseased specimen of rice representing 5 different sheath blight endemic locations were made. No significant morphological differences were observed among the isolates studied. The teleomorph of Rhizoctonia solani was not observed. Pairing of any two test isolates of R. solani resulted in hypha! anastomosis. Present isolates belonged to the same anastomosis group of AG-1.